Pain in Breast Cancer Treatment: Aggravating Factors and Coping Mechanisms - Maria de Fatima Guerreiro Godoy; Livia Maria Pereira de Godoy; Stelamarys Barufi; José Maria Pereira de Godoy (International Journal of Breast Cancer)
The objective of this study was to evaluate pain in women with breast cancer-related lymphedema and the characteristics of aggravating factors and coping mechanisms. The study was conducted in the Clinica Godoy, São Jose do Rio Preto, with a group of 46 women who had undergone surgery for the treatment of breast cancer. The following variables were evaluated: type and length of surgery; number of radiotherapy and chemotherapy sessions; continued feeling of the removed breast (phantom limb), infection, intensity of pain, and factors that improve and worsen the pain. The percentage of events was used for statistical analysis. About half the participants (52.1%) performed modified radical surgery, with 91.3% removing only one breast; 82.6% of the participants did not perform breast reconstruction surgery. Insignificant pain was reported by 32.60% of the women and 67.3% said they suffered pain; it was mild in 28.8% of the cases (scale 1–5), moderate in 34.8% (scale 6–9), and severe in 4.3%. The main mechanisms used to cope with pain were painkillers in 41.30% of participants, rest in 21.73%, religious ceremonies in 17.39%, and chatting with friends in 8.69%. In conclusion, many mastectomized patients with lymphedema complain of pain, but pain is often underrecognized and undertreated.